How collective self-esteem affects out-group trust in specific domains. - Sim, Miao Qin. (2012)
This paper aims to investigate how, upon perceiving a threat to one’s social identity in an important domain, out-group trust is affected by collective self-esteem and contingent collective self-worth. Out-group trust was hypothesized to have a positive relationship with domain-specific collective self-esteem (Hypothesis 1a), which would be more pronounced in people with high contingent collective self-worth (Hypothesis 1b). Out-group trust was also hypothesized to have a negative relationship with contingent collective self-worth (Hypothesis 1c). Based on the contact hypothesis, it was hypothesized that intergroup contact would mediate the relationship between domain-specific collective self-esteem and out-group trust as well (Hypothesis 2). All hypotheses were predicted to be specific to the Mathematics domain, an important aspect of Singaporean identity, but not in the Fine Arts domain or in general. A questionnaire study was conducted and results did not support the hypotheses. Domain-specific collective self-esteem and contingent collective self-worth were unrelated to out-group trust in the Mathematic domains. However, significant results were found in the Fine Arts domain and in general contexts; specifically, only Singaporeans with low contingent collective self-worth showed a positive relationship between domain-specific collective self-esteem and out-group trust. Mediation by intergroup contact was not supported, but intergroup contact consistently predicted out-group trust. This paper adds to the sparse literature on domain-specificity in collective self-esteem and out-group trust, and has implications for intergroup relations as well as the importance of contingent collective self-worth.